Is value-based health care just the latest fad or can it transform the Slovenian health care system? - Prevolnik Rupel, Valentina (Zdravstveno varstvo, 2023)
You get what you pay for is a very old saying, originating from England in the mid-to late 1800s. However, despite being in use for more than two centuries, its meaning is still not fully grasped in Slovenian healthcare. While we claim that the healthcare system serves the patient and that the care provided is patient-centred, we do not even measure the treatment outcomes that matter to patients. Without measuring these, we do not know whether the treatment provided value to the patients, i.e. what were the benefits of the treatment relative to the costs. Slovenian payment models do not reimburse the providers for created patient-relevant value, but rather for the planned number of services or cases based on average incurred costs. It is thus time to digitalise the system, and start collecting, curating and analysing the relevant data to ensure that all stakeholders within the healthcare system co-deliver value to patients. While relevant stakeholders highlight notable challenges of implementing value-based healthcare in Slovenia, these are far from insurmountable.
Keywords: analiza; analysis; benchmarking; data; digitalizacija; digitalization; financial incentives; finančne spodbude; health care; health system; payment mechanisms; plačilni mehanizmi; podatki; primerjave; Slovenia; Slovenija; zdravstvena oskrba; zdravstveni sistem